Mesin ayak dua saluran dilengkapi pengarah untuk beras jagung - Yohanes Benediktus Yokasing; Amiruddin Abdullah; Stanislaus Tamelab (University of Muhammadiyah Jakarta, 2022)
Sieve machine is used to separate groups of granules based on size. Most separation sieves on 2 groups of sifted/filtered grains move immediately, but the unfiltered grains are removed by the operator turning the sieve sideways or lifting the unfiltered material. In addition, the sifted material is usually poured directly on the sieve wire. This slows down the sifting process and the buildup can damage the sieve. On the other hand, sieve materials such as corn rice products, require 2 sizes of sieve wire holes. For that, do the design, made and studied the function,